A profile of poverty in Egypt - Datt, Gaurav; Jolliffe, Dean; Sharma, Manohar (Wiley, 2001)
This paper presents a profile of poverty in Egypt for 1997. It assesses the magnitude of poverty and its distribution across geographic and socioeconomic groups, provides information on the characteristics of the poor, illustrates the heterogeneity amongst the poor, and helps identify empirical correlates of poverty. This poverty profile is constructed using data from the Egypt Integrated Household Survey (EIHS), which is a nationwide, multiple-topic household survey. One of the more striking set of findings relates to the differences between the poor and the non-poor in their educational attainments. Our results indicate a significant literacy and schooling gap between the poor and the non-poor. On average the poor have 2.6 fewer years of schooling than the non-poor, and their literacy rate is 27 percent lower than the non-poor. Our results also indicate that augmenting educational attainment of the poor does not require building more schools, but reducing the poor s opportunity cost of attending schools and increasing their returns from extra schooling, both suggesting the importance of income generating activities as a policy instrument.